TAX POLICY OF THE SOVIET GOVERNMENT IN UZBEKISTAN (оn the example of 1950-1970) (Scientific journal of the Fergana State University, 2023)
The article analyzes the use of archival sources and various scientific literature on the example of the Uzbek SSR, misorganization of the work of accounting for taxpayers and their income, incomplete information on the size of farms, collective farms.